2022
DOI: 10.54501/jots.v1i2.29
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Child Sexual Abuse Material Users Contacting Children Online

Abstract: This study explores a sample of 1,546 anonymous individuals who voluntarily responded to our "Help us to help you" survey when searching for child sexual abuse material (CSAM) on the dark web. Nearly half (42%) of the respondents reported that they had sought direct contact with children through online platforms after viewing CSAM, and 58% reported feeling afraid that viewing CSAM might lead to sexual acts with a child or adult. This study analyses whether certain risk factors are linked to a higher likelihood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…Several forums on Darknet allow people with a sexual interest in children to anonymously gather and discuss or share CSAM ( Kloess and Bruggen, 2021 ). A recent Darknet survey indicated that many users report seeking direct online contact with children for sexual purposes after viewing CSAM ( Insoll et al, 2022 ). Also, 49 % reported thoughts of self-harm or attempting suicide, and 52 % difficulties in handling emotions and stress ( Insoll et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several forums on Darknet allow people with a sexual interest in children to anonymously gather and discuss or share CSAM ( Kloess and Bruggen, 2021 ). A recent Darknet survey indicated that many users report seeking direct online contact with children for sexual purposes after viewing CSAM ( Insoll et al, 2022 ). Also, 49 % reported thoughts of self-harm or attempting suicide, and 52 % difficulties in handling emotions and stress ( Insoll et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…While directly validating our estimates with information on the actual commune-level consumption of CSAM in France is not possible due to the lack of ground truth data, we indirectly validate our findings by correlating the cpc estimates with an appropriate proxy indicator, in our case commune-level statistics on the number of victims of sexual violence (both adults and minors) per 1000 inhabitants for communes within our study area. Recalling the link between CSAM consumption and sexual violence against children indicated by Eke et al ( 2011), Insoll et al (2022) and Hall and Hall (2007) in Section "Introduction" and assuming that a non-negligible fraction of victims of sexual violence are minors, we expect our cpc estimates to show stronger correlations with our proxy than general mobile consumption patterns of e.g., YouTube. However, we stress that this proxy most likely just captures the tip of the iceberg of sexual child abuse: First, the indicator includes rape, attempted rape, and sexual assault including sexual harassment.…”
Section: Methodsmentioning
confidence: 88%
“…Second, recalling from above, there is a strong empirical link between the consumption of CSAM and being involved in sexual violence against children. As Insoll et al (2022) points out: 42% of survey respondents in their study who have viewed CSAM tried to connect with children online afterwards. Therefore, knowledge about local patterns of CSAM consumption in the darknet may also inform about the prevalence of sexual violence against children in the physical world.…”
Section: "Dmentioning
confidence: 99%
“…The fact that CSAM is easy to access through the Tor network—and other anonymous networks—increases the likelihood that more children will be sexually abused: one study found that 41.8% (N = 647 of 1546) of anonymous people who answered a survey after searching for CSAM on Tor search engines said they had tried to seek direct contact with children online after viewing CSAM, and 57.9% (N = 895 of 1546) said they were afraid that viewing CSAM could lead to sexual acts with a child 8 . This suggests that roughly half of CSAM users do not expect to become offline offenders, which is relevant for subsequent public health interventions, as this may indicate a separation between the populations of online-only offenders and online and in-person offenders.…”
Section: Introductionmentioning
confidence: 99%